2018
DOI: 10.17310/ntj.2018.1.01
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Financial Shocks of Natural Disasters

Abstract: This paper employs panel vector autoregression to examine the dynamic fiscal response to disaster shocks. With 50-state, 1970-2013 panel data of state government finance and disaster damage, we estimate disaster impacts on revenue, expenditure, debt issuance, and intergovernmental transfers. We find that following a disaster, states increase program expenditure, but receive more federal transfers. Disasters have limited impact on total tax revenues but amplify fluctuations in sales, income, and property tax re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 51 publications
5
61
1
3
Order By: Relevance
“…First, this research only examines the impact of disasters on the current year's financial condition. Recent studies find that disasters have lagged impacts on government finances (Miao, Hou, and Abrigo ). FEMA disaster assistance may also be received in the years after disasters occur (Hildreth ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, this research only examines the impact of disasters on the current year's financial condition. Recent studies find that disasters have lagged impacts on government finances (Miao, Hou, and Abrigo ). FEMA disaster assistance may also be received in the years after disasters occur (Hildreth ).…”
Section: Resultsmentioning
confidence: 99%
“…Some scholars also find a positive impact of disasters in terms of their reconstruction stimulus (Loayza et al ). Disasters are found to increase intergovernmental transfers and increase the fluctuation of general sales, income, and property tax revenues (Miao, Hou, and Abrigo ). Spending on capital assets and social welfare also increases immediately following disasters (Miao, Hou, and Abrigo ).…”
Section: Governments’ Activities After a Natural Disaster Occursmentioning
confidence: 99%
“…Building on the previous work on elections and disaster declarations, this study explores whether there is a relationship between politics and the use of state funds. In particular, we are interested in the controversy and political pressure to dip into RDFs for relief (Reuters, ) and that disasters trigger significant increases in state expenditures (Miao, Hou, and Abrigo, ), which may affect savings. Therefore, we test the following series of hypotheses: Hypothesis 1 (H1) : The greater the disaster damage in a particular state the more the state has drawn down the RDF. Hypothesis 2 (H2) : The greater the disaster relief funds received by a particular state the less the state draws down its RDF. Hypothesis 3 (H3) : In an election year, where both governor and control of the state's legislature are the same party (either Democrat or Republican), the disaster damage and RDF association will be amplified (RDF balance will be drawn down further). Hypothesis 4 (H4) : When the majority control of Congress and the governor are of the same party (either Democrat or Republican), the disaster relief funds received and RDF association will be amplified (RDF balance will be drawn down even less). …”
Section: The Purpose Of State Stabilization Funds (Also Known As Rdfs)mentioning
confidence: 99%
“…In addition to the short-run budgetary impacts of paying for emergency and clean-up costs and additional health and welfare expenses, Johnson (2014) notes that local revenue sources such as property and sales taxes may be affected in both the short and long runs. On the positive side, a recent paper on the effect of natural disasters on state finances, Miao, Hou, and Abrigo (2016), finds that state sales tax revenues rise initially after a disaster rather than fall, presumably as citizens prepare for and respond to the disaster. Moreover, they find that in the long run there is no significant effect of natural disasters on state sales tax revenues.…”
Section: Local Government Vulnerability To Sea-level Risementioning
confidence: 99%
“…To our knowledge, there has not been a formal analysis of the extent to which local governments incur unreimbursed expenses from natural disasters. However, a recent study of the effect of natural disasters on state finances byMiao, Hou, and Abrigo (2016) found that even though states receive significant amounts of transfers from multiple agencies of the federal government in response to a natural disaster, the increases in public spending on health and welfare in a state is larger than the federal transfers, resulting in a net negative effect on state finances.6 According toFannin and Detre (2012) it typically takes between three months and two years for FEMA to reimburse local governments.…”
mentioning
confidence: 99%